Fostering Religious Character through the Implementation of School Culture in Pancasila Student Profiles - Susanti, Atika; Darmansyah, Ady; Muktadir, Abdul (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
Internalization of religious values in education is a crucial aspect of shaping students' character and morals. One effective way to achieve this is through habituation activities integrated into the school culture. This research aims to describe the formation of religious character through the implementation of school culture in Pancasila student profiles. The research method used is qualitative descriptive, conducted at elementary school 44 Bengkulu City. Research subjects include the school principal, teachers, and students. Data collection instruments include observation guidelines, interview sheets, and documents. The data analysis process includes data collection, data condensation, data presentation, and drawing conclusions. The research findings indicate that the religious dimension in Pancasila student profiles has been effectively implemented through school culture. This is evident in exemplary habituation policies involving both verbal and non-verbal actions such as dressing neatly, displaying politeness, being disciplined in worship, and practicing 6S (Smile, Salute, Greet, Polite, Courteous, and charity). Additionally, there are spontaneous habits such as praying before starting lessons, and the integration of intracurricular learning through subjects in the Merdeka curriculum such as Islamic Religious Education and Pancasila Education. Extracurricular activities like scouting serve as a means to embody religious values. These findings emphasize that a school culture incorporating religious values can positively contribute to the development of students' religious character